A long-wavelength xanthene dye for photoacoustic imaging. Issue 85 (5th October 2022) - Zhou, Xinqi; Fang, Yuan; Wimalasiri, Viranga; Stains, Cliff I.; Miller, Evan W.
Abstract : Xanthene dyes are repurposed for photoacoustic (PA) imaging by the introduction of an sp 2 hybridized ketone group. The new dyes exhibit remarkable PA signal at 860 nm and can be multiplexed with indocyanine green (ICG) in blood. Abstract : Photoacoustic (PA) imaging is a powerful biomedical imaging modality. We designed KeTMR and KeJuR, two xanthene-based dyes that were readily obtained through a 2-step synthetic route. KeJuR has low molecular weight, good aqueous solubility, and superior chemical stability compared to KeTMR . KeJuR shows a robust PA signal under 860 nm excitation and can be paired with traditional PA dyes for multiplex imaging in blood samples under a tissue-mimicking environment.